STUDENTS’ PERCEPTION OF USING ‘MEDIUM’ TO PROMOTE READING INTEREST: A CASE STUDY IN THE ENGLISH EDUCATION AT SRIWIJAYA UNIVERSITY - Zalfa Rabila Qatrunnada; Tita Ratna Wulan Dari (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aimed to find out students’ perceptions of using Medium to promote reading interest in the English education study program at Sriwijaya University. A case study of a qualitative method was applied in this study. The research instruments used in this study were a close-ended questionnaire and a semi-structured interview. A total of 50 participants from 2, 4, 6, and 8 semester in English Education, Sriwijaya University joined the questionnaires and 5 selected participants participated in the interview. The data from questionnaire were analysed using percentage, while the data from interview were analysed using thematical analysis. Methodological triangulation used in this study to analysed both data source, in order to link in the answer from questionnaire and interview. The findings showed that the majority of students (78%) had positive experience regarding their experience in using Medium. They reported Medium help them to promote their reading interest citing its accessibility, diverse content, and ease of use as key advantages.